2019
DOI: 10.30957/ijoltl.v4i3.607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of E-learning Based Schoology on the Learning Outcomes in Nursing Program

Abstract: The fast advance of information technology has attempted English teachers with innovative and recent teaching models. This study focuses on the use of Schoology in ESP nursing class. The quantitative research was done with one group pre-test and post-test design. The samples were the second semester ESP class of Nursing program as an experimental group that consists of 122 students and 122 students as a control group. The instruments used the test to measure the students’ cognitive achievement. The inferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Focusing on the implementation of e-learning platforms in English teaching context, (Tigowati, Efendi, A., & Budiyanto, 2017) found that students' cognitive performance was higher after they were taught by using Schoology. By the same token, (Rachman, D., Sunarti, 2019) study revealed that Schoology also contributed to the improvement of students' English learning outcomes at the Nursing Program. Then, some researchers emphasized the students' perception.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Focusing on the implementation of e-learning platforms in English teaching context, (Tigowati, Efendi, A., & Budiyanto, 2017) found that students' cognitive performance was higher after they were taught by using Schoology. By the same token, (Rachman, D., Sunarti, 2019) study revealed that Schoology also contributed to the improvement of students' English learning outcomes at the Nursing Program. Then, some researchers emphasized the students' perception.…”
Section: Introductionmentioning
confidence: 90%
“…In the Indonesian EFL setting, several studies have been conducted related to online learning. To mention some, (Atmojo, A. E. P., & Nugroho, 2020;Bali, S., & Liu, 2018;Basri, M., & Paramma, 2019;Cakrawati, 2017;Mudra, 2018;Rachman, D., Sunarti, 2019;Tigowati, Efendi, A., & Budiyanto, 2017), may represent the trend. Focusing on the implementation of e-learning platforms in English teaching context, (Tigowati, Efendi, A., & Budiyanto, 2017) found that students' cognitive performance was higher after they were taught by using Schoology.…”
Section: Introductionmentioning
confidence: 99%
“…Learning Media During the Covid-19 Pandemic at SDN Ciater 1 continues as it is. E-Learning is a technology that has made a major contribution to the improvement of the learning process (Rachman, 2019). Distance learning is nothing new, technology has made a major contribution to improving the learning process.…”
Section: Introductionmentioning
confidence: 99%